Hertzian contact damage in silicon nitride ceramics with different porosity contents. Issue 8 (August 2015) - Azeggagh, N.; Joly-Pottuz, L.; Nélias, D.; Chevalier, J.; Omori, M.; Hashida, T.
Abstract This work investigates the Hertzian contact damage in Si3N4 ceramics with 3 and 18% porosity processed by spark plasma sintering technique. Low densification was achieved by sintering at pressures lower than needed for a full density. The indentation tests were performed using diamond spheres of various sizes to evaluate the Hertzian contact damage at different scales. Surface damage was observed under electron microscopy while subsurface damage was examined using focused ion beam sectioning technique. Different failure modes were noticed, depending on the size of the volume solicited and the porosity content. At small scale, short cracks initiate from the existing pores then coalesce leading to a quasi-plastic failure mode. At larger scale and for high porosity content, surface ring and radial cracks usually observed for dense brittle materials vanish; the damage mode is mostly related to the fragile rupture of bridges between collapsed pores.